A expansão das perífrases de gerúndio no português brasileiro - Basilio, Jucilene Oliveira Sousa (2011)
In this survey the variation that exists in the use of periphrasis along with the present continuous of the Brazilian Portuguese is investigated under the light of Variationist Sociolinguistics to make a boundary in the systematization of the linguistic variation in which the structure be+present continuous (estar+gerúndio) is inserted in the following fields: present, infinitive non-future and infinitive future. These areas build variable potential models of the discursive genre register. We tried to understand which factors influenced the alternation in the customary present field ( along with habitual reading), in constructions as “ …how do you always forget everything… we are insisting on calling you to hang on the party…”; infinitive , on enunciations like “…the secretary came here to be signing the current document…”; and, the future infinitive in structures like this “It is about the seminary we are going to be talking first”. Taking as reference a corpus drew from the non-orthodox Labov’s variation methodology, we got results through a statistic elaboration of data in the programs Varbrul, version GoldVarb X, that generated the effects showed on this survey.